Management control over foreign subsidiaries : a comparative case study of two Finnish MNCs operating in the United States - Lietzen, Jannina (My University, 2019)
Due to the internationalization movement, companies have been establishing foreign subsidiaries across the globe. This movement has raised the question of how foreign subsidiaries can be managed at a distance from headquarters. Headquarters’ control of subsidiary operations is a central integrating function in all multinational companies (MNC). Several MNCs have experienced challenges when operating in the United States, and mainly the challenges are caused by insufficient or unsuitable management control over foreign operations. Therefore, management control over subsidiaries located in the United States becomes extremely important. Headquarters, as the principal decides which control mechanisms are used and how much autonomy the foreign subsidiary i.e. the agent has. The aim of this thesis is to examine the management control process over foreign subsidiaries. In particular, the objective is to study how MNCs from Finland manage subsidiaries located in the United States. The thesis uses a case-based approach and studies the management control processes in two Finnish MNCs that have established subsidiaries in the United States. Drawing on the object of control framework by Merchant and Van der Stede (2007), this thesis attempts to portray and explain the use of different control mechanisms in the multinational context. This thesis also studies how different control mechanisms complement each other. Moreover, this thesis examines how the control process is affected by factors related to the MNC, the foreign subsidiary and the relationship between these two entities. This study has a number of findings. Firstly, the role of the subsidiary and the environment where the subsidiary operates influence the management control process over foreign subsidiaries. Secondly, cultural differences play a role when conducting informal control over foreign subsidiaries. Formal mechanisms, notably different accounting tools, are generally suitable mechanisms to manage subsidiaries located in the United States. Lastly, this thesis supports the complementary use of control mechanisms. Most MNCs use a variety of different control mechanisms to manage foreign subsidiaries. Formal control can be complemented with informal control mechanisms. In addition, different formal control mechanisms can complement each other, and they are not mutually exclusive. Altogether, it can be concluded that control over foreign subsidiaries can be met by several management control system designs.
Keywords: management control, multinational company, foreign subsidiary